DAMPAK AKUMULASI SAMPAH PLASTIK TERHADAP KUALITAS FISIK, KIMIA, DAN BIOLOGI EKOSISTEM MANGROVE PASAR BANGGI, KABUPATEN REMBANG - , YODHI FAISAL AMIN, Ni Putu Diana Mahayani, S.Hut., M.For. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mangrove forest can be observed in Pasar Banggi village,which is part of mangrove ecosystem, along the north coast of Rembang Regency.The accumulation of solid waste consisted mostly of plasticthat originated from fisherman's ships waste, may pollute the mangroveecosystem of Pasar Banggi. Therefore,this study aimed to (1) identify the relationship betweenthe accumulation of plastic waste and the physical, chemical, and biologicalcharacteristics of the mangrovehabitat, (2) identify the relationship between the accumulation of plastic waste andthe vegetation density of mangrove ecosystem at PasarBanggi, Rembang Regency. A systematic sampling approach was applied by clasifying the area into grids of 40x40 m. One plot was established in each grid to identify between temperature, pH,salinity, dissolved oxygen, turbidity, organic content, macrobentos,and vegetation density. In total, there were 30plots which consisted of 15 plots without plastic waste observed and 15 plots accumulated plastic waste. were measured from each plot. All parameter were then compared between those observed from plots with and without accumulated plastic waste using t-test analysis. Regression analysis was applied to identify the relationship between the accumulation of plastic waste and the physical, chemical, and biological habitat quality and vegetation density of the mangrove ecosystem. The results showthat the average of water temperature, water salinity, and pH were below the allowed water quality standards.However, the rate of turbidity and organic content were above the allowed water quality standards. The vegetation density was classified as high (> 1500 tree/acres), eventhough the plastic waste accumulation can be found in the mangrove area. There was significant difference in water salinity and organic content in the substratebetween plots without accumulated plastic wasteand with accumulated plastic waste. It showed the accumulated plastic waste have significant effect on water salinity and organic content in the mangrovesubstrate.